Cyberbullying: Varian Perundungan terhadap Anak Berbasis Digital - Irfan Irfan (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
The digital era, as it is today, with an easily accessible internet network, creates conveniences for people to communicate or exchange information. Digital technology which is increasingly sophisticated today, has a significant influence on changes in people's lives, and various digital technologies have sprung up along with the progress and needs of the times. Positive and negative impacts must always accompany every development; this is not the case with technological developments. One of the subjects who are connoisseurs of technological developments that are feared to have a negative impact is children because, at the age of a child, which is a stormy transitional phase in the inner life of children, it is feared that it can make their psyche very unstable and easily influenced by external influences so that the age of this child is very vulnerable to violence both in the real world and in cyberspace, both physical and non-physical. One form of violence that children in cyberspace often experience is cyberbullying. Cyberbullying is an act or behavior of a person or group that is carried out intentionally and repeatedly (continuously) to carry out actions that hurt other people through computers, cell phones and other electronic devices that impact the psychological condition of the victim